TRANSLATING THE PROSECUTOR INTO A LEGAL ATTACHE IN INDONESIAN DIPLOMATIC LEGAL TEXTS - Johannes Ronald Elyeser Roparulian Hutagalung; Pujiyono Suwadi (Conscientia - Journal on Language, Literature, and Culture, 2026)
This article examines legal attaché as a borrowed term operating within Indonesian diplomatic legal discourse. It traces the gap between established international institutional referents and the nationally specific concept the term is used to designate, namely Atase Kejaksaan, the prosecutor seconded to an Indonesian embassy abroad. The study draws on a corpus of primary documents from December 2025, including the Hague Conference on Private International Law (HCCH) record of Indonesia's application for membership dated 4 December 2025, an English-language report by the Indonesian National Police (INP) on 150 Indonesian nationals facing capital punishment in Malaysia dated 3 December 2025, and the statutory and regulatory corpus of the Indonesian prosecution service. The analysis traces how the borrowed term behaves across three institutional registers: U.S. federal law enforcement, international organisational administration, and Indonesian diplomatic practice. Drawing on Newmark's (1988) translation procedures, Šarčević's (1997) account of institutional non-equivalence, Tiersma's (1999) analysis of legal language, and Prieto Ramos's (2021) inter-systemic incongruity framework, the article argues that legal attaché is terminologically underdetermined as a rendering of Atase Kejaksaan. The borrowed term imports institutional associations drawn from the FBI's law enforcement attaché programme and from international organisation practice that are structurally incompatible with the Indonesian official's prosecutorial identity, appointment mechanism, and normative mandate. The December 2025 documents supply concrete evidence of this terminological slippage. The article proposes descriptive and qualified rendering strategies for legal translators and diplomatic drafters handling Indonesian prosecutorial titles in formal bilateral and multilateral instruments.